Система суб’єктів превентивної діяльності та місце в ній органів Національної поліції України - Беспалий, І. В.; Bespalyi, I. V. (Вісник Кримінологічної Асоціації України. - 2024. - № 1 (31). - С. 731–739, 2024)
Запропоновано авторське визначення поняття суб’єктів превентивної діяльності. Здійснено аналіз норм чинного законодавства, на основі чого виділено три великі групи суб’єктів превентивної діяльності. З’ясовано, що суб’єкти превентивної діяльності – це сукупність, визначених нормами чинного законодавства, органів державної влади та їх посадових осіб, а також структурних підрозділів поліції, які наділені необхідною компетенцією та повноваженнями для реалізації спеціальних заході та вчинення особливого роду дій, спрямованих на профілактику, запобігання та попередження порушень режиму законності в державі, а також прав, свобод та інтересів людини і громадянина.

It was found that the subjects of preventive activity are a set of state authorities and their officials, as well as structural subdivisions of the police, which are endowed with the necessary competence and powers to implement special measures and perform a special type of actions aimed at prevention, defined by the norms of current legislation , preventing and preventing violations of the rule of law in the state, as well as the rights, freedoms and interests of a person and a citizen. It is argued that the subject structure of preventive activity includes three groups: 1) the Verkhovna Rada of Ukraine, the Cabinet of Ministers of Ukraine, the Ministry of Internal Affairs of Ukraine - subjects of ensuring and creating conditions for the implementation of preventive activities of the National Police; 2) local state administrations and local self-government bodies – subjects of support and assistance in the implementation of preventive activities by the National Police of Ukraine; 3) specially authorized bodies and units of the National Police of Ukraine are the key actors of prevention, which are responsible for the actual implementation of special measures, means, operations and actions aimed at the prevention, prevention and prevention of violations of the rule of law, human and citizen rights and freedoms. It is emphasized that the peculiarity of each subject of all three groups is that they have the opportunity to enter into administrative and legal relations on issues of provision, organization and implementation of preventive activities, they have the opportunity exclusively in accordance with their competence and powers, which are of a heterogeneous nature and are strictly regulated by legislation of Ukraine.

Предложено авторское определение понятия субъектов превентивной деятельности. Осуществлен анализ норм действующего законодательства, на основе чего выделены три большие группы субъектов превентивной деятельности. Выяснено, что субъекты превентивной деятельности – это совокупность, определенная нормами действующего законодательства, органов государственной власти и их должностных лиц, а также структурных подразделений полиции, которые наделены необходимой компетенцией и полномочиями для реализации специальных мероприятии и совершения особого рода действий, направленных на профилактику, предотвращение и предупреждение нарушений режима законности в государстве, а также прав, свобод и интересов человека и гражданина.
The system of subjects of preventive activities and the place in it of National police bodies of Ukraine
Keywords: система; суб’єкт; превентивна діяльність; Національна поліція України; адміністративно-правовий статус; system; subject; preventive activity; National Police of Ukraine; administrative and legal status; субъект; превентивная деятельность; Национальная полиция Украины; административно-правовой статус